The Role of Attending Center-Based Care for Kindergarten-Aged Children with Disabilities. Issue 2 (February 2017) - Gottfried, Michael A.
Background/Context: Families have been increasingly utilizing center-based care both during prekindergarten as well as before/after school during kindergarten (CBC-K), and the literature has addressed the relative effectiveness of attending the former on early schooling outcomes. However, missing in the field is an analysis of the efficacy of attending the latter. To compound this, no research has considered how attending CBC-K is associated with early outcomes for children with disabilities. Purpose/Objective/Research Question/Focus of the Study: There were four research questions: 1. Do kindergarten academic outcomes differ for children with disabilities who did and did not attend CBC-K? 2. Do kindergarten socioemotional outcomes differ for children with disabilities who did and did not attend CBC-K? 3. Do these relationships differ by disability? 4. Do these relationships differ by socioeconomic status (SES)? Population/Participants/Subjects: This study utilizes data from the newly released Early Childhood Longitudinal Study – Kindergarten Class of 2011, which represents the most contemporary national-level data available to study these research questions. Research Design: This study examined two sets of outcomes. The first set included reading and math achievement. The second set included socioemotional scales based on both teacher and parent ratings of child behavior. These outcomes were regressed on a measure for having attended CBC-K as well as a wide span of child and family characteristics. Error terms were clustered at the school level to account for nested data. Findings: The results based on the first and second research questions indicated that for children with disabilities, there was a negative association between attending CBC-K and academic and socioemotional measures compared to not attending CBC-K. As for the third research question, children with emotional or learning/communication disabilities had the largest observed negative association with the set of outcomes from having attended CBC-K (along with children with developmental delays when considering achievement outcomes) compared to children from the same groups who did not attend CBC-K. As for the fourth research question, there was little difference of attending versus not attending CBC-K by SES. Conclusions/Recommendations: When considering transitions into kindergarten, attending CBC-K certainly appears to have an effect, albeit negative for both children with and without disabilities. Having documented these patterns, this study helped to provide a well-rounded portrait into how center-based care affects outcomes for school-aged children.